Space time coding schemes for 4 or more antennas - Correia, Américo (2019)
In this paper we present a new space time transmit diversity (STTD) scheme for M4 transmit antennas and one receive antenna. The new diversity scheme belongs to the open loop class and consists of an extension to the work presented in [1,2,3]. Another hybrid scheme that combines open and close loop classes is also presented. The coding rate of the new scheme is one and in spite of the presence of inter-symbol interference it may achieve the full diversity after applying a multi-dimensional orthonormal rotation to the original constellation. For each coding scheme every block with 8 received symbols is detected using a maximum likelihood decoding algorithm to get the estimated maximum likelihood sequence. Q-QAM modulations are analysed.